2011
DOI: 10.1143/jjap.50.025002
|View full text |Cite
|
Sign up to set email alerts
|

Size Reduction and Phosphorus Doping of Silicon Nanocrystals Prepared by a Very High Frequency Plasma Deposition System

Abstract: In this paper, we describe the size reduction and phosphorus doping of silicon nanocrystals (SiNCs) fabricated using a very high frequency (VHF) plasma deposition system. The size reduction of SiNCs is achieved by changing the VHF plasma power. The size of SiNCs changes from 10 to 5 nm. We discuss the relationship between VHF plasma power and the size of SiNCs in terms of radicals in the VHF plasma, such as SiH3, SiH2, SiH, and H. On the other hand, we have fabricated phosphorus-doped SiNCs by adding PH3 gas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…For a review on the experimental results regarding doping efficiency and electrical activity of doped Si-NCs the reader is referred to Refs: [89,90]. The doped Si-NCs have a good crystallinity, showing that the lattice spacing with respect to undoped Si-NCs is not affected for P-doped Si-NCs, whereas it is slightly reduced for B-doped ones, owing to the smaller size of the B atom [114,123] Experiments pointed out that the hyperfine splitting (HFS) shows a clear size dependence [130] and that impurities are mainly incorporated in substitutional sites [114,120,131,132,134]. Still regarding the dopant location, several studied pointed out that B atoms prefer to stay in the Si-NC core, whereas P atoms prefer to reside at the Si-NC surface [110,122,135] Regarding the PL intensity, in the case of B doping there is a decrease with an increase in the doping concentration, whereas for P-doping the intensity becomes smaller at small P concentration and subsequently increases at large concentration [110,114] (see the bottom panel of Fig.…”
Section: Free-standing Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a review on the experimental results regarding doping efficiency and electrical activity of doped Si-NCs the reader is referred to Refs: [89,90]. The doped Si-NCs have a good crystallinity, showing that the lattice spacing with respect to undoped Si-NCs is not affected for P-doped Si-NCs, whereas it is slightly reduced for B-doped ones, owing to the smaller size of the B atom [114,123] Experiments pointed out that the hyperfine splitting (HFS) shows a clear size dependence [130] and that impurities are mainly incorporated in substitutional sites [114,120,131,132,134]. Still regarding the dopant location, several studied pointed out that B atoms prefer to stay in the Si-NC core, whereas P atoms prefer to reside at the Si-NC surface [110,122,135] Regarding the PL intensity, in the case of B doping there is a decrease with an increase in the doping concentration, whereas for P-doping the intensity becomes smaller at small P concentration and subsequently increases at large concentration [110,114] (see the bottom panel of Fig.…”
Section: Free-standing Nanocrystalsmentioning
confidence: 99%
“…The second one, implementing a supercell approach, requires large cells (thus large vacuum regions) to prevent interactions between a NC and its image. Moreover in the case of charged systems, the reciprocal space approach requires a procedure to neutralise the background Si-NC (one follows this procedure because both EPR [134] and EDMR [131] have demonstrated that impurities are not interstitials). By taking into account only one impurity per Si-NC one can simulate a wide range of high doping concentrations, which vary approximately from 2x10 20 cm 3 (1 mol%) to 7x10 21 cm 3 (20 mol%).…”
Section: Ab-initio Calculations: Formation Energies Role Of Sizes Smentioning
confidence: 99%
“…However, as pointed out above, it is difficult from the experimental point of view to obtain information about the exact dopant location, nevertheless different techniques have been employed in order to obtain information about the position of the impurity atoms. Electron paramagnetic resonance (EPR) has been used to demonstrate that P impurities are incorporated in substitutional sites, a conclusion reached also by electrically detected magnetic resonance (EDMR) . Regarding B impurity it has been found that the incorporation of B in the Si‐NCs is much less efficient with respect to the case of P .…”
Section: Free‐standing Si‐ncsmentioning
confidence: 99%
“…3 Additionally, it offers the possibility of dopant (P,B) incorporation during growth. [10][11][12][13] Although silane is usually chosen as a precursor for plasma synthesis, SiCl 4 has also been suggested as a cheaper and safer alternative. 7,8 Nanocrystals grown from a SiCl 4 /H 2 /Ar mixture are terminated with a mixture of chlorine and hydrogen, with variable fractions depending on the plasma composition and reactor pressure.…”
Section: Introductionmentioning
confidence: 99%